PENGARUH PERHATIAN ORANG TUA TERHADAP PENYESUAIAN DIRI MAHASISWA BARU PRODI BIMBINGAN DAN KONSELING ANGKATAN 2023 DI UNIVERSITAS JAMBI - Mel, Melani; Rasimin, Rasimin; Lubis, Muhammad Alridho (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2024)
The research entitled The Effect of Parental Attention on Self-Adjustment of New Students of the Guidance and Counseling Study Program class of 2023 at Jambi University. In the process of self-adjustment, students can face problems of acceptance and rejection in adjustment or association. Self-adjustment is a process that includes mental and behavioral responses, which are individual efforts to successfully overcome needs, stress, conflicts. The purpose of this study was to determine the level of parental attention and the level of self-adjustment of new students and to reveal the effect of parental attention on the self-adjustment of new students of the guidance and counseling study program class of 2023 at Jambi University. Researchers who have previously conducted pre-research on new students of the Guidance and Counseling Study Program class of 2023 at Jambi University found that many new students have difficulty adapting to a new environment and have problems in self-adjustment, especially when socializing. This type of research is expost facto research with a quantitative approach. The population in this study were all new students of Guidance and Counseling class 2023 at Jambi University as many as 111 people. The sampling technique used was simple random sampling with a confidence level of α.0.05 with the Slovin formula, the sample obtained was 87 respondents divided into 3 classes. Data collection tools used in research. The calculation results obtained in this study indicate that the level of parental attention is at a "high" level with an overall percentage of 72.5% and for self-adjustment is at a "high" level with a percentage value of 77.2%. The results showed that the parental attention variable (X) had an influence on the variable (Y) of 21.5% which is interpreted as having a "strong enough" influence.